Understanding the nexus between the politics of patronage and political repression in North African rentier states: a comparative study of the Algerian and Egyptian governments' approaches to the 2011 Arab spring - Nhlengethwa, Thabane (My University, 2018)
In a bid to fathom the prevalence of authoritarian rule in Middle Eastern and North African (MENA) states, Iranian economist, Hossein Mahdavy, postulated the Rentier State Theory (RST) in 1970. The theory attributed the endurance of autocracy, in the region, to the vast availability of resource rents - which are purportedly used by the rentier states to preserve their dictatorial rule. The RST’s cogency would later find profounder cognitive consolidation in Michael Ross’s critically acclaimed journal article, “Does Oil Hinder Democracy?”, wherein he made compelling extrapolations on the causal mechanisms of the theory by applying a triad of effects: the ‘rentier’, ‘taxation’, and ‘modernisation’ effects. Leveraging Mahdavy and Ross’s inferrences as a point of departure, the study investigates why the 2011 Arab Spring undermined the fundamental premises of the RST by forcing regime change, and in some cases, democratic reforms in North Africa. A comparative case study analysis of how two North African Rentier States, Algeria and Egypt, confronted the 2011 popular uprisings is conducted in order to underscore the value and importance of development-orientated resource rents redistribution to regime survival.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in International Relations (CW & RR) at The University of the Witwatersrand, Johannesburg February 2018
Keywords: Arab Spring, 2010-; Protest movements--Africa, North--21st century; Algeria--Politics and government--21st century; Egypt--Politics and government--21st century